2021
DOI: 10.21203/rs.3.rs-619178/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple Bronchiolar Adenomas With Malignant Transformation and CCNE1 Mutation: a Case Report and Literature Review

Abstract: Background: Bronchiolar adenoma (BA) is a recently proposed diagnostic terminology, which is considered as the expansion of the concept of ciliated muconodular papillary tumors (CMPT). BA is considered to be a benign neoplasm, but a few previous cases have been reported with the possibility of malignant transformation. Therefore,the genetic and histological nature of BA is controversial so far. We describe a rare case of multiple BAs with malignant transformation and CCNE1(cyclin E1)mutation to increase the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…7 According to previous studies, driver mutations or malignant transformation in BA/CMPT have been reported in several cases. [1][2][3][4][5][8][9][10][11] It is therefore controversial whether BA/CMPT is benign or malignant. In reported cases that showed malignant transformation, the lack of continuity of basal cells and the recognition of the same driver mutation were considered to be grounds for malignant transformation of BA/CMPT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 According to previous studies, driver mutations or malignant transformation in BA/CMPT have been reported in several cases. [1][2][3][4][5][8][9][10][11] It is therefore controversial whether BA/CMPT is benign or malignant. In reported cases that showed malignant transformation, the lack of continuity of basal cells and the recognition of the same driver mutation were considered to be grounds for malignant transformation of BA/CMPT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some cases with driver mutations or malignant transformation have been observed. [1][2][3][4][5] Thus, whether BA/CMPT is benign or malignant is considered controversial. We herein report an extremely rare case of a 68-year-old woman with a CMPT accompanied by adenocarcinoma in situ (AIS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the high mutation frequency of BA driver genes, the skip growth pattern, characteristic micropapillary structure, and the simultaneous coexistence with IMA with the same driver gene mutation [5,6,12,13], which makes whether BA can act as a precancerous lesion as a hot topic for current discussion. In this case, we report the simultaneous presence of mutations in KRAS (G12V) in the BA and IMA regions.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the evidence of BA as a precancerous lesion there are some the published literatures (Table 2), Han [6] et al found that sequencing analysis of the region of BA and IMA showed that KRAS mutation (G12V) occurred in both parts, so it is further inferred that IMA originate from BA, in other words BA malignant transformation to IMA. Li [13] et al reported a case of CCNE1 (Exon7, c.476A > G) mutation in mixed GGN and pure GGN with mutation abundances of 48.83% and 45.41%, respectively.…”
Section: Discussionmentioning
confidence: 99%